Association of Hyper-Polypharmacy With Clinical Outcomes in Heart Failure With Preserved Ejection Fraction. (November 2021) - Minamisawa, Masatoshi; Claggett, Brian; Suzuki, Kota; Hegde, Sheila M.; Shah, Amil M.; Desai, Akshay S.; Lewis, Eldrin F.; Shah, Sanjiv J.; Sweitzer, Nancy K.; Fang, James C.; Anand, Inder S.; O'Meara, Eileen; et al.
Abstract : Background: Polypharmacy is associated with a poor prognosis in the elderly, however, information on the association of polypharmacy with cardiovascular outcomes in heart failure with preserved ejection fraction is sparse. This study sought to investigate the relationship between polypharmacy and adverse cardiovascular events in patients with heart failure with preserved ejection fraction. Methods: Baseline total number of medications was determined in 1758 patients with heart failure with preserved ejection fraction enrolled in the Americas regions of the TOPCAT trial (Treatment of Preserved Cardiac Function Heart Failure With an Aldosterone Antagonist), by 3 categories: nonpolypharmacy (<5 medications), polypharmacy (5–9), and hyper-polypharmacy (≥10). We examined the relationship of polypharmacy status with the primary outcome (cardiovascular death, HF hospitalization, or aborted cardiac arrest), hospitalizations for any reason, and serious adverse events. Results: The proportion of patients taking 5 or more medications was 92.5% (inclusive of polypharmacy [38.7%] and hyper-polypharmacy [53.8%]). Over a 2.9-year median follow-up, compared with patients with polypharmacy, hyper-polypharmacy was associated with an increased risk for the primary outcome, hospitalization for any reason and any serious adverse events in the univariable analysis, but not significantly associated with mortality. After multivariable adjustment for demographic and comorbidities, hyper-polypharmacy remained significantly associated with an increased risk for hospitalization for any reason (hazard ratio, 1.22 [95% CI, 1.05–1.41]; P =0.009) and any serious adverse events (hazard ratio, 1.23 [95% CI, 1.07–1.42]; P =0.005), whereas the primary outcome was no longer statistically significant. Conclusions: Hyper-polypharmacy was common and associated with an elevated risk of hospitalization for any reason and any serious adverse events in patients with heart failure with preserved ejection fraction. There were no significant associations between polypharmacy status and mortality. Abstract : Supplemental Digital Content is available in the text.